2021
DOI: 10.3390/ijerph18147324
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Limb Jump Asymmetries and Their Association with Sport-Specific Performance in Young Male and Female Swimmers

Abstract: This study aimed to examine inter-limb jump asymmetries and their association with sport-specific performance in young swimmers. Thirty-eight (male, n = 19; female, n = 19) regional/national level young swimmers (age: 12.3 ± 1.2 years; height: 159.6 ± 8.2 cm; body mass: 52.5 ± 9.2 kg) participated in this study. Inter-limb asymmetries were assessed for single-leg countermovement jump (SLCMJ) and single-leg standing long jump (SLSLJ). Sport-specific performance was evaluated using front crawl (i.e., 50 m and 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…From these, only 1 verified significant negative correlation ( r −0.70 to −0.83) between asymmetries and swimming performance (expressed as takeoff velocity from the block) (23). The other 3 studies did not show significant correlations between asymmetries and swimming velocity, 50- and 25-m front crawl time, or 50- and 25-m kick time (62,65,66).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…From these, only 1 verified significant negative correlation ( r −0.70 to −0.83) between asymmetries and swimming performance (expressed as takeoff velocity from the block) (23). The other 3 studies did not show significant correlations between asymmetries and swimming velocity, 50- and 25-m front crawl time, or 50- and 25-m kick time (62,65,66).…”
Section: Resultsmentioning
confidence: 90%
“…In addition, given that asymmetry is a ratio number (i.e., made up of 2 parts), establishing the direction of an asymmetry (i.e., dominance) provides additional context as to how each limb is performing and can be advantageous (10). Among the studies analyzed in this review, only one investigated the individual direction of asymmetry and reported the coefficient of variation, using it to interpret the values of asymmetry (62). The authors verified that although the coefficient of variation values were acceptable (<10%), less than 50% of the tested athletes presented asymmetry scores above the coefficient of variation, indicating no “real” between-limb differences in over half of the sample (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, muscle strength and power (e.g. jumping from the starting block and flip turns in swimmers) play a relevant role in competitive performance [13][14][15]. For example, up to large associations (r = 0.40 to 0.70) have been reported between 20-and 50-m front crawl swimming performance and mean propulsive power in jump squat [16], leg extension strength [17], and horizontal jump distance [18].…”
Section: Introductionmentioning
confidence: 99%
“…Child height is an important indicator of human capital and human development (Alves Junior et al, 2021). Health is the beginning of life for humans (Phukan et al, 2021;Sulaiman et al, 2020). Nutrition received by the body can shape the child's height and provide health (Vyas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%